Highly Active and Stable Immobilized Iridium Complexes via Thermochemically Assisted Dangling Oxygen Participation for Electrochemical Oxygen Evolution Reaction - Chae, Sang Youn; Choi, Myeong Jin; Lee, Si Young; Choi, Ja Yoon; Kim, Dae Won; Lee, Je Seung; Park, Eun Duck; Yoo, Jong Suk; Joo, Oh Shim (Small Science, 2025)
This study investigates the immobilization of dinuclear iridium-imidazole complexes onto indium tin oxides for the electrochemical oxygen evolution reaction (OER) in acidic media. The immobilized iridium complexes show exceptional catalytic activity and stability, which are attributed to the facile cleavage of the elongated μO bonds between the two iridium metal centers. This cleavage leads to the formation of dangling oxygen, which plays a crucial role in facilitating thermochemical water dissociation. O2 is released through a dangling oxygen–participated mechanism, accompanied by the regeneration of the μO bonds. This unique OER mechanism, possibly specific to immobilized (strained) molecular catalysts, resembles the lattice oxygen participation mechanism reported for unstable oxides, but with the advantage of high stability in acidic media. This study not only identifies a new mechanism but can also inform the design of immobilized molecular catalysts with enhanced performance.
Keywords: in situ Raman spectroscopy; lattice oxygen participation mechanism; molecular complexes; oxygen evolution reaction; μ-oxo bridges